Quantitative Productivity Analysis Of Broiler Farming Business With System Closed House And System Open House - Pradiptha, Nizham; Mudawamah; Umi Kulsum, (UNIVERSITAS ISLAM LAMONGAN, 2025)
This research was conducted in Banjarmasin City, South Kalimantan Province. The study was conducted in October 2023. The objective was to analyze the differences in quantitative productivity between broiler farms maintained under closed and open house systems. The subjects used in the study were 180,000 broilers raised in 15 cages each, each with a population of 6,000 birds per cage. This research was conducted at the broiler partnership farm of PT Mitra Sinar Jaya. The research method used a quantitative descriptive approach, with data obtained from the maintenance records of partner farmers. The number of recordings came from 6,000 broilers per cage, with 15 replications for each type of closed house and open house. The quantitative productivity observed in this study were depletion (mortality + culling), number of birds harvested, Feed Intake (FI), average harvest body weight (ABW), Feed Conversion Ratio (FCR), harvest age, cage density, and Performance Index (IP). Data were analyzed using an Independent t-test. Based on the results of the study, it shows that depletion, the number of harvested chickens, ABW, FCR, FI, broiler harvest age have no significant differences (P>0.05) between closed house and open house cages. While in quantitative productivity, cage density and IP there are differences between broilers raised with closed house and open house cage systems. From the average value there is a tendency for closed houses to be better than open houses seen from the depletion value which is better by 63 heads (174 heads vs. 237 heads); the number of harvested chickens is better by 63 heads (5826 heads vs. 5763 heads); FI is better by 0.034 (2.798 kg/head vs. 2.832 kg/head); ABW is better by 0.05 kg (1.79 kg and 1.74 kg); FCR is better by 0.068 (1.555 kg feed/kg bw vs. 1.623 kg feed/kg bw); A better cage density of 4 birds/m² (13 birds/m² vs. 9 birds/m²) and a 27-point higher Performance Index (PI) (350 vs. 323), except for the same harvest age (32 days vs. 32 days).The conclusion of this study is that the depletion value, number of birds harvested, Feed Intake (FI), ABW, FCR, and cage density of broilers using a closed house system tend to be better than those using an open house system. The success rate of broiler farming is achieved by farmers using a closed house system because the Performance Index (PI) value is higher than that of farmers using an open house system. Based on the research results, which show that closed houses tend to be 8.35% better than open houses, it is recommended that farmers using closed and open house systems improve the quality of human resources and record keeping as a basis for continuous management evaluation to achieve optimal productivity.